2003
DOI: 10.1126/science.1086050
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Region-Wide Declines in Caribbean Corals

Abstract: We report a massive region-wide decline of corals across the entire Caribbean basin, with the average hard coral cover on reefs being reduced by 80%, from about 50% to 10% cover, in three decades. Our meta-analysis shows that patterns of change in coral cover are variable across time periods but largely consistent across subregions, suggesting that local causes have operated with some degree of synchrony on a region-wide scale. Although the rate of coral loss has slowed in the past decade compared to the 1980s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,413
4
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,810 publications
(1,458 citation statements)
references
References 13 publications
22
1,413
4
19
Order By: Relevance
“…The ecology of Caribbean and western Atlantic coral reefs has changed dramatically in recent decades and it is now believed that these reefs are in crisis (Rogers 1985;Wilkinson 1993;Ginsburg 1994;Brown 1997;Connell 1997;Eakin et al 1997;Aronson and Precht 2001a;Gardner et al 2003). This is especially true along the Florida reef tract (Shinn 1989;Ward 1990;Lidz 1997).…”
Section: The Problemmentioning
confidence: 93%
See 1 more Smart Citation
“…The ecology of Caribbean and western Atlantic coral reefs has changed dramatically in recent decades and it is now believed that these reefs are in crisis (Rogers 1985;Wilkinson 1993;Ginsburg 1994;Brown 1997;Connell 1997;Eakin et al 1997;Aronson and Precht 2001a;Gardner et al 2003). This is especially true along the Florida reef tract (Shinn 1989;Ward 1990;Lidz 1997).…”
Section: The Problemmentioning
confidence: 93%
“…It is becoming increasingly apparent that regional-and global-scale causes of reef decline are most important in structuring modern reef communities including those in Florida. Gardner et al (2003) used meta-analysis to assess the extent of coral decline across the Caribbean since the 1970s. Their results revealed that reefs from all regions were affected.…”
Section: Water Qualitymentioning
confidence: 99%
“…Some areas have suffered disproportionately: the Caribbean, for example, has lost 80% of its reefs since the 1970s (ref. 2). By the end of this century, researchers expect ocean waters to drop from a pH of 8.1 to 7.9 or lower, and to warm by at least 2 °C, averaged across the globe.…”
Section: In Hot Watermentioning
confidence: 99%
“…This absence is particularly 44 striking for temperate coastal ecosystems, which, ironically, support much of the world's human 45 population. Instead, most of our understanding of coastal change comes from small-scale 46 experiments and observations (Crain et al, 2008(Crain et al, , 2009), or from tropical systems such as coral 47 reefs (Gardner et al, 2003;De'ath et al, 2012). This knowledge gap vastly impedes our ability to 48 predict and avert the impacts of global change on key population centers, particularly given the fact 49 that stressors, and corresponding management actions, often occur at much larger scales.…”
Section: Introduction 37mentioning
confidence: 99%